2020
DOI: 10.4046/trd.2020.0033
|View full text |Cite
|
Sign up to set email alerts
|

Sputum Inflammometry to Manage Chronic Obstructive Pulmonary Disease Exacerbations: Beyond Guidelines

Abstract: Quantitative sputum cytometry facilitates in assessing the nature of bronchitis associated with exacerbations of chronic obstructive pulmonary disease (COPD). This is not assessed in most clinical trials that evaluate the effectiveness of strategies to prevent or to treat exacerbations. While up to a quarter of exacerbations may be associated with raised eosinophil numbers, the vast majority of exacerbations are associated with neutrophilic bronchitis that may indicate airway infections. While eosinophilia may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
(101 reference statements)
0
3
0
Order By: Relevance
“… 20 Pulmonary hemosiderosis associated with alveolar hemorrhage also has been associated with pulmonary hypertension associated with chronic lung inflammation, specifically pulmonary veno‐occlusive disease, generalized vasculitis and coagulation disorders in humans. 21 , 22 , 23 The presence of hemosiderophages in BALF cytology has been shown to be a sensitive and specific marker for left ventricular dysfunction in humans, 24 , 25 and high numbers of alveolar hemosiderophages have been found in human patients with congestive heart failure. 26 Studies in small animals, 8 mice, 27 and horses 28 have shown that damage to the pulmonary microcirculation and blood gas permeability related to pulmonary hypertension have been closely related to alveolar bleeding and consequent hemosiderosis.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Pulmonary hemosiderosis associated with alveolar hemorrhage also has been associated with pulmonary hypertension associated with chronic lung inflammation, specifically pulmonary veno‐occlusive disease, generalized vasculitis and coagulation disorders in humans. 21 , 22 , 23 The presence of hemosiderophages in BALF cytology has been shown to be a sensitive and specific marker for left ventricular dysfunction in humans, 24 , 25 and high numbers of alveolar hemosiderophages have been found in human patients with congestive heart failure. 26 Studies in small animals, 8 mice, 27 and horses 28 have shown that damage to the pulmonary microcirculation and blood gas permeability related to pulmonary hypertension have been closely related to alveolar bleeding and consequent hemosiderosis.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, Eltboli and Brightling ( 36 ) showed that in COPD patients, induced sputum can be used to assess airway inflammation for individuals suffering from the disease by performing differential cell counts and therefore allowing for a more tailored treatment and management and in diagnosing chronic lung diseases. A raised sputum neutrophilia combined with high sputum levels of TNF-α and IL-8 has been linked with COPD and is suggested as a potential marker for the diagnosis of COPD ( 2 , 37 ). Kirsch et al ( 38 ) showed that the analysis of induced sputum can be used in diagnosing Pneumocystis carinii (currently named Pneumocystis jirovecii ) pneumonia ( 38 , 39 ).…”
Section: Applications Of Induced Sputummentioning
confidence: 99%
“…Most importantly, in both pathologies, airway inflammation is considered their primary cause. It has been shown that improved understanding, management, and treatment of these respiratory diseases lie with the measurement of airway inflammation and, in some cases, the associated microbial infections (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%